Feasibility Assessment of Hydroelectric Power Plant in Ungauged River Basin: A Case Study - Tuna, M. Cihat (Springer Heidelberg, 2013)
The accurate estimation of long-term resource availability, as represented by discharge, is an essential component of hydropower constructions for generation capacity estimation as well as environment protection on ungauged river basins. Feasibility studies concerning decision-making for various types of items to be used in a hydropower plant on ungauged river basins are important in order to estimate the energy generation, the approximate cost of the project, and the required budget allocation. A feasibility study is necessary which evaluates the energy generation cost, investment and maintenance costs for hydropower projects. The purpose of this study is to analyze the technical feasibility of hydropower plant installations at ungauged sites. A case study is performed to illustrate this investigation. By means of the methodology presented in this research work, it will be possible to carry out sound and successful research to assess the economic feasibility of a hydropower project on ungauged river basins.
Keywords: Hydropower; Feasibility report; Ungauged river basin; Cost estimation; Income-expense ratio